Dollarization in Latin America : Recent Evidence and Some Policy Issues - Savastano, Miguel (Washington, D.C. : International Monetary Fund, 1996)
This paper examines the pattern of dollarization in Latin America, focusing on the experience of five countries (Argentina, Bolivia, Mexico, Peru and Uruguay) during 1970-1993. It presents evidence on the relative size of dollarization, the allocation of foreign currency deposits, and the behavior of money velocity. The discussion stresses the role of institutional factors, macroeconomic conditions, and the dynamics of money demand In shaping the dollarization process; it also highlights the shortcomings of indicators frequently employed to analyze the phenomenon. The paper provides a brief critical assessment of the empirical literature on dollarization, and identifies areas where further research seems warranted.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet